Mule Drivers in Nineteenth-Century Lebanon: from local social history towards Global History (Almanack, 2021)
This article makes the case for a project in the making: a study of the social transformation of the countryside as it joins the global market over the long nineteenth century, told as a collective biography of the mule drivers of Ottoman Lebanon those obscure peasants who, owning one or a few mules, made their livelihood in the transport of goods and persons rather than work the land. Over the first half of the century, these actors mobilized for revolts while a village-based economy turned to cash-crop agriculture and the central government built a new state apparatus that would insure its survival withim global capitalism, rendering the peasants' situation ever mora precarious. From the 1860s to the First World War, as local resources were diverted to feed European industry and local petty-trade networks came undone, when elites at all levels struggled to assert their control over labor and resources, these same muleteers turned into social bandits smugglers who d extraction. Some of them accumulated wealth and ultimately integrated an emerging middle class. The projected account makes two historiographical interventions. (a) Within the history of the modern Middle East, it argues that the region's confessional tensions are tied to developments that are characteristic of capitalism over the period namely, the rise of a new kind of state and the loss of control over resources by local actors at the margins. This approach pushes against purely culturalist explanations, attempting to wed culturalist and materialist stances. (b) Conversely, by drawing parallels with other mounted rural bandits in the Anatolian and Romanian hinterlands of the Ottoman Empire, as well as with the gauchos in Latin America, ox-cart drivers in India, and rickshaw pullers in China, this local history speaks to a global history of capitalism. Reducing the scale of analysis to reveal the subjectivity of local actors, and linking the cultural norms that shape agency to objective structural transformation that can be compared across contexts, this project challenges histories of capitalism that ignore the countryside or the global South and thereby produce a sanitized account characterized by secular politics and a liberal culture.